Properties of wood plastic composites made from rubberwood sawdust / Wan Mohd Norsafizu Wan Mohd Nor - Wan Mohd Nor, Wan Mohd Norsafizu (2012)
This research is aimed to investigate the mechanical and physical properties of the thermoplastic composite from the Rubberwood species. The strength properties were tested for water absorption rates, thickness swelling, bending, and tensile tests based on ASTM standards. In this study, two variables as the ratio of wood particles (10%, 20%, and 30%) and size of wood particles (150µm, 180µm, and 250µm) was performed. From the study, smaller size of wood particle and 10% of wood ratio exhibited the higher strength of wood plastic composite. From this study as well, the higher filler loading, will decrease the strength of wood plastic composite.